The alkaloids of Voacanga globosa (Blanco) Merrill - Lleander, Glory Coronado 1936-
The bark of Voacanga globosa (Blanco) Merrill was exhausted of its alkaloidal content by extracting it with different organic solvents. The weak bases were separated from the strong bases by chloroform extraction. The chloroform-soluble alkaloids were chromatographed over alumina and from this two crystalline bases have been isolated. They were provisionally referred to as Alkaloid I and II. Alkaloid I melts at 212(degrees), the UV-spectrum of which shows maximum absorption at 225 and 295 mu, while Alkaloid II melts at 295(degrees), with UV-spectrum showing maximum absorption at 220, 267, 300 and 325 mu. The above results, and elementary analyses, chromatograms, and IR-spectra of Alkaloids I and II show a close comparison with those of voacamine and vobtusine (isolated from Voacanga africana Stapf), respectively.